2018
DOI: 10.7567/jjap.57.106401
|View full text |Cite
|
Sign up to set email alerts
|

Optical, scintillation and radiation tolerance properties of Pr-doped pyrosilicate crystals

Abstract: A series of Pr-doped pyrosilicate crystals, Y2Si2O7 (YPS), Pr2Si2O7 (PrPS), Gd2Si2O7 (GPS), and Lu2Si2O7 (LPS), were synthesized by the floating zone (FZ) method to investigate whether the positive hysteresis phenomenon was observed or not. In all crystals, no impurity phases were observed in X-ray diffraction (XRD) analyses. In photoluminescence (PL) spectra, Pr3+ 5d–4f emission was observed from 270 to 400 nm in all the samples, and the PL decay times of them were around 10 ns. In radioluminescence (RL) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…In our most recent study, 140) we found that Pr-doped LPS did not show any positive hysteresis (confirmed by the pulse height analyses), and we thought that the positive hysteresis of the pioneering report in Pr-doped LPS may have been be affected by radiation-induced afterglow (their study was based on a radioluminescence analysis). Therefore, in my opinion, the materials confirmed to show positive hysteresis up to now are CsI, GSO and GAGG.…”
Section: Recent Randd Progress Of Scintillatorssupporting
confidence: 72%
“…In our most recent study, 140) we found that Pr-doped LPS did not show any positive hysteresis (confirmed by the pulse height analyses), and we thought that the positive hysteresis of the pioneering report in Pr-doped LPS may have been be affected by radiation-induced afterglow (their study was based on a radioluminescence analysis). Therefore, in my opinion, the materials confirmed to show positive hysteresis up to now are CsI, GSO and GAGG.…”
Section: Recent Randd Progress Of Scintillatorssupporting
confidence: 72%
“…Finally, the signals were sent to a personal computer. In the PH analysis, the scintillation light yield was calibrated using 1.0 mol% Pr-doped LPS, which had a light yield of 9700 ph/MeV (28) with a similar emission spectrum to that of Pr-doped GPS. The linearity and energy resolution were evaluated using the same setting to that of various γ-ray sources such as 22 Na (511 keV), 57 Co (122 keV), 133 Ba (356 keV), 137 Cs (662 keV), and 241 Am (60 keV).…”
Section: Methodsmentioning
confidence: 99%
“…The broad emission from 340 to 410 nm originated from the 5d-4f transition of Pr 3+ . (28,34) The scintillation decay time profiles are shown in Fig. 6.…”
Section: Sample Synthesismentioning
confidence: 99%
See 2 more Smart Citations